2013
DOI: 10.1159/000347147
|View full text |Cite
|
Sign up to set email alerts
|

Association between Milder Brain Deformation before a Shunt Operation and Improvement in Cognition and Gait in Idiopathic Normal Pressure Hydrocephalus

Abstract: We investigated the association between the degree of deformation of the brain before shunt operation and improvement of gait and cognitive impairment after shunt operation in 16 patients with idiopathic normal pressure hydrocephalus (iNPH). We evaluated gait and cognitive impairment and measured the cerebrospinal fluid volume in the ventricles/sylvian fissure (vVS) and the subarachnoid space at high convexity/midline areas (vHCM) using MR images with voxel-based morphometry before and 3 months after shunt ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 72 publications
0
11
0
1
Order By: Relevance
“…The MRI scans did not show any changes in diameter and cross‐sectional area of the midbrain after shunting . Because shunting has been proven to improve gait function in NPH patients, the lack of change in midbrain diameter reported by Hiraoka et al . serves as evidence that refutes the original hypothesis that midbrain abnormalities are associated with gait dysfunction in NPH.…”
Section: Pathophysiology Of Gaitmentioning
confidence: 79%
“…The MRI scans did not show any changes in diameter and cross‐sectional area of the midbrain after shunting . Because shunting has been proven to improve gait function in NPH patients, the lack of change in midbrain diameter reported by Hiraoka et al . serves as evidence that refutes the original hypothesis that midbrain abnormalities are associated with gait dysfunction in NPH.…”
Section: Pathophysiology Of Gaitmentioning
confidence: 79%
“…First, the number of participants was small. Second, we used the ROI method to avoid distortion problems because of severe brain deformation of patients with iNPH . Such distortions affect voxel‐based statistical image analyzing methods, such as statistical parametric mapping, and therefore we could not evaluate rCBF across the whole brain.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found long-term improvement of cognitive functions after shunt surgery [ 34 , 35 , 36 , 37 ], while others failed to demonstrate such an improvement [ 14 , 20 , 38 ]. However, comparability between studies is hampered both by the use of different neuropsychological test batteries and different time intervals between intervention and neuropsychological assessment.…”
Section: Discussionmentioning
confidence: 99%